Extração de compostos bioativos da semente de cumaru (Dipteryx odorata) utilizando fluidos pressurizados - Lima, Jéssica de Carvalho (2014)
The coumarin (benzopyrone), is an active principle with characteristic aroma, similar to vanilla. It has bronchodilator, anti-inflammatory and analgesic effect, besides being used in cosmetics and as a flavoring. It is widely distributed in fruits like strawberry, cherry, apricot and vegetables, as guaco chestnut India, emburana, watercress, cinnamon and tonka bean. The seed cumaru (Dipteryx odorata), in turn, is found in the northern region of Brazil, used in naturopathy and cuisine and its pharmaceutical potential has not yet been adequately explored. The application of active ingredients in the pharmaceutical industry requires that the present compound extracted is free of solvent residues and has high purity. In this sense this paper aims to obtain selectively coumarin from tonka bean seed. For this, the study of equilibrium phase at high pressures in order to determine the behavior of {CO2 + coumarin} system and determine the conditions favorable for the handling of this compound using carbon dioxide was performed. In conducting the study phase equilibria visual synthetic method was used, the temperature and mole fraction ranges from 25ºC to 65ºC and 2x10-3 to 6x10-3, respectively. The phase transition pressure values ranged from 58.45 bar to 198.66 bar. The extraction technique with pressurized fluids to obtain the coumarin from cumaru seed seen that presents the possibility for the substitution of organic non-toxic gases such as carbon dioxide solvent was used, resulting in a reduced environmental impact extraction, to obtain a product free of residual solvents, ensuring consumer safety and avoiding additional spending on product separation and solvent. The temperature chosen for extraction ranged between 60°C e 80 º C and pressures between 180 bar e 220 bar. The co-solvents dichloromethane, ethyl acetate and ethanol was used in percentages 1%, 3% and 5%, in order to increase the dissolving power of the fluid in the vegetable matrix. The kinetics of extraction were satisfactorily represented by the mathematical model Sovová by comparing the calculated and experimental data. Further extractions with organic solvents ethanol and hexane Soxhlet through in order to evaluate the efficiency of the appliance with high pressure were performed. All extracts obtained from the cumaru seed were analyzed qualitatively and quantitatively by means of liquid chromatography and gas chromatography. Finally, the extract from the supercritical carbon dioxide using co-solvents was more selective than the classical extraction, proved to be a promising method for obtaining coumarin from Dipteryx odorada seed.